Evaluation of different methods detecting intracellular generation of free radicals - Wilhelm, Jirí; Vytásek, Richard; Ostádalová, Ivana; Vajner, Ludĕk (Molecular and cellular biochemistry, 2009)
Reactive oxygen species (ROS) play several biological roles. We investigated the applicability of fluorescent probes for their detection (i) in rabbit lens epithelial cells during ageing in culture, and (ii) in thin sections of rat heart. We used dihydroethidium (DHE), dichlorofluorescin (DCFH), and dihydrorhodamine 123 (DHR) together with detection of autofluorescence both in cells and in chloroform extracts. Superoxide production was confirmed by a specific histochemical method using Mn(2+). All methods demonstrated higher production of ROS in older cells. All probes revealed different sites of ROS production in young and old cells and could be used for investigation of ROS generation during cell ageing. In the thin sections of rat heart DCFH was not suitable for intracellular ROS detection. The results indicate that the potential of fluorescent dyes in ROS detection is not usually fully exploited, and that blue autofluorescence is associated with oxidative damage.
Keywords: Fluoresceins; reaktivní formy kyslíku; Ethidium; volné radikály; Methods; Molecular Probe Techniques; krysa rodu Rattus; epitelové buňky; Lens, Crystalline; zvířata; Free Radicals; Reactive Oxygen Species; ethidium; molekulární sondy - techniky; rhodaminy; Epithelial Cells; fluoresceiny; metody; králíci; Rats; myokard; Animals; Myocardium; oční čočka; Rabbits; Rhodamines